Effect of immunological castration of male pigs on morphological and functional condition of the testicles - Samoiluk, V. V.; Samoylyuk, Vyacheslav; Samoyuluk, V. V.; Samoylyuk, V.; Samoylyuk, V. V.; Samoylyuk, Wyacheslav; Samoylyuс, W. W.; Samoiliuk, V. V.; Samoiliuk, V.; Самойлюк, Вячеслав Володимирович; Koziy, M. S.; Козій, М. С.; et al. (Дніпровський нац. ун-т ім. О. Гончара, 2021)
The paper presents a morpho-functional substantiation of the expediency of immunological castration in the conditions of industrial pork production. The effect of immunological castration with Improvac on the morphological and functional state of boar testes was studied. Testosterone levels were determined by radioimmunology 2, 4, 6, 8 weeks after immunological and surgical castration, as well as in uncastrated boars of the control group. At slaughter, testicular biopaths were selected from immunological castrates and control boars for histological examination. Testosterone levels 2 weeks after castration were lowest in animals castrated with Improvak. This rate gradually increased and after 8 weeks was higher than in surgically castrated. In the latter, testosterone levels gradually decreased over 8 weeks, and in uncastrated boars during this period did not change significantly. The last stages of spermatogenesis in immunological castrates are suppressed after the second vaccination. As a result of immunological castration, the interstitial tissue of the testis undergoes certain changes. Between the tubules there is a growth of loose unformed connective tissue. Leydig cells lose the hyperchromaticity of the cytoplasm and the typical polygonal profile, their functional potential decreases. This fact is confirmed by changes in the Gertwig constant. Namely, there is a decrease in the value of the nuclear-cytoplasmic ratio. There is a shift in the time of the mitotic cycle, a low degree of differentiation of spermatogonia and stopping the subsequent stages of spermatogenesis. However, primary spermatogonia and single cell divisions reproduce, and single spermatids can be found in the convoluted tubules. Some of them form specific spherical and elliptical cell groups in the seminal tubules. These structures are absent in the testes of control animals. Microstructural changes in pigs after the introduction of Improvak are characterized by a lack of Leydig cells, which indicates the absence of a normal hormonal background and is confirmed by the results of a study of testosterone levels. The epithelial-spermatogenic layer is underdeveloped, and the lumens of the tubules are sometimes filled with generations of spermatocytes. Meiosis is observed locally in places, which also indicates insignificant functioning of the testes. Improvac vaccination causes significant testicular atrophy in pigs and a decrease in their functional status, which allows us to recommend it for wider use in Ukraine as an alternative to surgical castration. Вивчали вплив імунологічної кастрації Імпроваком на морфологічний і функціональний стан сім’яників кнурів. Рівень тестостерону визначали радіоімунологічним методом через 2, 4, 6, 8 тижнів після імунологічної та хірургічної кастрації, а також у некастрованих кнурів контрольної групи. Під час забою були відібрані біопати сім’яників у імунологічних кастратів та кнурів контрольної групи для гістологічного дослідження. Рівень тестостерону через 2 тижні після кастрації був найнижчим у тварин кастрованих Імпроваком. Цей показник поступово підвищувався і через 8 тижнів був вищим ніж у кастрованих хірургічно. У останніх рівень тестостерону поступово знижувався протягом 8 тижнів, а у некастрованих кнурів в ці терміни суттєво не змінювався. Останні стадії сперматогенезу у імунологічних кастратів пригнічуються після другої вакцинації. Внаслідок імунологічної кастрації інтерстиціальна тканина сім’яника зазнає певних змін. Між канальцями спостерігається розростання пухкої неоформленої сполучної тканини. Клітини Лейдига втрачають гіперхроматичність цитоплазми і типовий полігональний профіль, знижується їх функціональний потенціал. Цей факт підтверджується змінами константи Гертвіга. А саме, спостерігається зменшення значення ядерно-цитоплазматичного співвідношення. Має місце зміщення часу мітотичного циклу, низька ступінь диференціації сперматогоній і зупинка перебігу наступних стадій сперматогенезу. Але все ж відбувається розмноження первинних сперматогоній і поодинокі клітинні розподіли та в звивистих канальцях можна знайти поодинокі сперматиди. Деякі з них утворюють специфічні клітинні угрупування кулястої та еліптичної форми у сім’яних канальцях. Дані структури відсутні у сім’яниках контрольних тварин. Мікроструктурні зміни у свиней після введення Імпроваку характеризуються нестачею клітин Лейдига, що свідчить про відсутність нормального гормонального тла і підтверджується результатами дослідження рівня тестостерону. Епітеліально-сперматогенний шар недорозвинений, а просвіти канальців місцями заповнені генераціями сперматоцитів. Місцями локально відмічається мейоз, що також свідчить про незначне функціонування сім’яників. Вакцинація Імпроваком викликає значну атрофію сім’яників у свиней та зниження їх функціонального стану.
Вплив імунологічної кастрації кнурів на морфологічну і функціональну здатність сім’яників
Самойлюк Вячеслав Володимирович https://orcid.org/0000-0001-8400-8904 Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384 Масліков Сергій Миколайович https://orcid.org/0000-0003-1353-3968 Спіцина Тетяна Леонідівна https://orcid.org/0000-0002-8047-7305 Галузіна Людмила Ігорівна http://orcid.org/0000-0003-0478-0027
Keywords: seminiferous tubules; сім’яні трубочки; Improvak; Імпровак; testosterone level; рівень тестостерону; Leydig cells; клітини Лейдига; spermatogonia; сперматогонії; spermatids; сперматиди